One-pot synthesis of g-C3N4/MnO2 and g-C3N4/SnO2 hybrid nanocomposites for supercapacitor applications. Issue 10 (3rd August 2018) - Kavil, Jithesh; Anjana, P. M.; Periyat, Pradeepan; Rakhi, R. B.
Abstract : Incorporation of MnO2 nanostructures as spacers enhances the electrochemical energy storage performance of g-C3 N4 . The g-C3 N4 /MnO2 composite electrode exhibited a specific capacitance of 174 F g −1 . Abstract : Carbon materials with layered structures with their unique surface area and charge transport properties have been attracting significant attention as electrode materials in renewable energy storage devices. The rapid agglomeration of layered materials during electrochemical processes reduces their shelf life and specific capacitance, which can be prevented by the introduction of suitable spacers between the layers. Herein, we report the electrochemical performance of MnO2 and SnO2 metal oxide spacers incorporated layered graphitic carbon nitride g-C3 N4 in a symmetric two electrode configuration. The as-prepared g-C3 N4 /MnO2 and g-C3 N4 /SnO2 hybrid nanocomposites act as efficient electrode materials for symmetric supercapacitors. The performance of the electrode materials is compared with that of bare g-C3 N4 . A remarkable increase in specific capacitance was obtained for the g-C3 N4 /MnO2 composite electrode (174 F g −1 ) when compared to the bare g-C3 N4 electrode (50 F g −1 ) and g-C3 N4 /SnO2 electrode (64 F g −1 ). At a constant power density of 1 kW kg −1 the symmetric supercapacitors based on g-C3 N4, g-C3 N4 /SnO2, and g-C3 N4 /MnO2 electrodes exhibited energy densities of 6.9, 8.8 and 24.1 W h kg −1 respectively.